2011
DOI: 10.1016/j.jcm.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The presence of extensor digiti medii muscle—anatomical variant

Abstract: Objective: This study reports the presence of the extensor digiti medii muscle (EDM) in a population of cadavers dissected by students at a chiropractic college anatomy laboratory and determines its frequency, bilaterality, innervation, and sex differences. Methods: Dissection of upper extremities of 47 human cadavers (24 males, 23 females) was conducted. Both upper extremities were examined for bilaterality. The long extensor tendons were exposed, separated, and cut to expose the EDM. Identifying the innervat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Four studies reported the gender composition of their results [5,23,42,45]; out of 37 EMP, 16 were found in males and 22 in females. Four studies reported the side composition of their results [5,10,23,42]; out of 31 EMP, 7 were bilateral, and 17 unilateral of which 11 were on the right side and 6 on the left side.…”
Section: The Prevalence Of Empmentioning
confidence: 99%
“…Four studies reported the gender composition of their results [5,23,42,45]; out of 37 EMP, 16 were found in males and 22 in females. Four studies reported the side composition of their results [5,10,23,42]; out of 31 EMP, 7 were bilateral, and 17 unilateral of which 11 were on the right side and 6 on the left side.…”
Section: The Prevalence Of Empmentioning
confidence: 99%
“…The incidence of EMP has been reported to be 1% to 12% in cadaver studies, in the current study it is 9.3%. Table1 reports the incidence of EMP in literature [13,[15][16][17][18]. EMP is observed more frequently in males than females, but it is not frequently described in anatomical dissections since it is a small muscle in width and is covered by the tendons of ED [19].…”
Section: Discussionmentioning
confidence: 99%
“…Authors & Year of study Country Number. of specimens Incidence % Von Schroeder and Botte (1995) [13] California 43 12 Jonathan S. Carlos (2011) [15] Southern California 94 7.4 Dass et al(2011) [16] Indian 100 9 Suwannakhan A et al (2016) [17] Thailand 100 8 K. Ozturk et al (2020) [18] Turkey The EDBM can be a good source for tendon transfer for restoration of malfunctioning muscles like in case of damaged extensor pollicis longus [24]. A close physical examination of hand for differential diagnosis of tenosynovitis or a ganglion cyst becomes imperative where in the ganglion becomes prominent with wrist flexion and in active extension EDBM becomes prominent [23].…”
Section: Extensor Digitorum Brevis Manusmentioning
confidence: 99%
“…Becoming thoroughly acquainted with the extensor tendons' variants may be helpful for hand surgeons in planning tendon graft surgery [3,25] and allowing them to successfully perform tenosynovectomy for the treatment of de Quervain's syndrome [3,19]. The detailed anatomical knowledge of the extensor tendons is a determining factor in preserving healthy tendons during orthopedic procedures, hence accounts for good patient outcomes and improves their quality of life [3,5].…”
Section: Introductionmentioning
confidence: 99%